Готический замок Дракулы. Не стой на пути вампира!: повести / Е. В. Артамонова - Артамонова Елена Вадимовна (Золотая коллекция Страшилок, 2004)
Экземпляры: Д.О. (20191018) / Инвентарный номер: 40104 / Цена: 70.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: А86 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44